2018
DOI: 10.5195/jyd.2018.607
|View full text |Cite
|
Sign up to set email alerts
|

Camp Research: What? So What? What’s Next?

Abstract: This special issue of the Journal of Youth Development provides a means to highlight where camp research is today based on the articles presented. Several common areas are identified: role of theory, addressing social issues, methodological imagination, emerging audiences, samples, linking operations and outcomes research, staff and youth development, moving outcomes from what to how, and thoughtful and intentional implications for practice. Areas that need additional consideration in future camp research and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Despite this, Henderson et al (2007) completed a review on camp research, concluding that the major areas of camp study included operations (i.e., physical, and emotional health, and safety of participants) and outcome research (i.e., self-esteem and independence, social skills, physical and thinking skills, positive values, and spirituality). Later, Henderson (2018) admitted that most of the existing camp research has focused on participants' outcomes, criticizing this focus as being overly generic. Most camps expose participants to new and challenging experiences to promote growth, and these experiences often result in positive child development (THURBER, 2007).…”
Section: Gaps In Child Camps' Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite this, Henderson et al (2007) completed a review on camp research, concluding that the major areas of camp study included operations (i.e., physical, and emotional health, and safety of participants) and outcome research (i.e., self-esteem and independence, social skills, physical and thinking skills, positive values, and spirituality). Later, Henderson (2018) admitted that most of the existing camp research has focused on participants' outcomes, criticizing this focus as being overly generic. Most camps expose participants to new and challenging experiences to promote growth, and these experiences often result in positive child development (THURBER, 2007).…”
Section: Gaps In Child Camps' Researchmentioning
confidence: 99%
“…They noted the importance of documenting best practices and alerted for challenges in camp-related research: reliable instruments to measure camp experience; parental Management of child camps: a structured literature review and new directions 13 permission to avoid intrusiveness; control of children to prevent the effects of peer and/or staff influence; sampling strategies to examine different camp experiences and larger samples. Henderson (2018) extended his prior work by conducting a thorough review of research related to camp experiences and identified nine "direct contributions to better understanding camp experiences" (p. 318). These directions included theory, social issues, methodological imagination, emerging audiences, samples, linking operations and outcomes, and staff/youth development.…”
Section: Camp Researchmentioning
confidence: 99%
See 3 more Smart Citations